Genetic structure in the European endemic seabird, Phalacrocorax aristotelis, shaped by a complex interaction of historical and contemporary, physical and nonphysical drivers. Issue 10 (8th March 2017) - Thanou, Evanthia; Sponza, Stefano; Nelson, Emily J.; Perry, Annika; Wanless, Sarah; Daunt, Francis; Cavers, Stephen
Abstract: Geographically separated populations tend to be less connected by gene flow, as a result of physical or nonphysical barriers preventing dispersal, and this can lead to genetic structure. In this context, highly mobile organisms such as seabirds are interesting because the small effect of physical barriers means nonphysical ones may be relatively more important. Here, we use microsatellite and mitochondrial data to explore the genetic structure and phylogeography of Atlantic and Mediterranean populations of a European endemic seabird, the European shag, Phalacrocorax aristotelis, and identify the primary drivers of their diversification. Analyses of mitochondrial markers revealed three phylogenetic lineages grouping the North Atlantic, Spanish/Corsican and eastern Mediterranean populations, apparently arising from fragmentation during the Pleistocene followed by range expansion. These traces of historical fragmentation were also evident in the genetic structure estimated by microsatellite markers, despite significant contemporary gene flow among adjacent populations. Stronger genetic structure, probably promoted by landscape, philopatry and local adaptation, was found among distant populations and those separated by physical and ecological barriers. This study highlights the enduring effect of Pleistocene climatic changes on shag populations, especially within the Mediterranean Basin, and suggests a role for cryptic northern refugia, as well as known southern refugia, on the genetic structure of European seabirds. Finally, it outlines how contemporary ecological barriers and behavioural traits may maintain population divergence, despite long‐distance dispersal triggered by extreme environmental conditions (e.g. population crashes).